1995
DOI: 10.1074/jbc.270.24.14541
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Elongation Factor Tu Prevents Ternary Complex Formation

Abstract: The elongation factor Tu (EF-Tu) is a member of the GTP/GDP-binding proteins and interacts with various partners during the elongation cycle of protein biosynthesis thereby mediating the correct binding of amino-acylated transfer RNA (aa-tRNA) to the acceptor site (A-site) of the ribosome. After GTP hydrolysis EF-Tu is released in its GDP-bound state. In vivo, EF-Tu is post-translationally modified by phosphorylation. Here we report that the phosphorylation of EF-Tu by a ribosome associated kinase activity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…A number of in vitro targets of PrpC are proteins involved in translation, including EF-Tu, EF-G, and CpgA (1,50). EF-Tu is also a substrate of the eSTP Stp in Listeria monocytogenes (4,5). Thus, while eSTPs appear to modulate processes involved in growth, the mechanistic basis of this regulation is not well understood.…”
Section: Ppm Family Estpsmentioning
confidence: 99%
“…A number of in vitro targets of PrpC are proteins involved in translation, including EF-Tu, EF-G, and CpgA (1,50). EF-Tu is also a substrate of the eSTP Stp in Listeria monocytogenes (4,5). Thus, while eSTPs appear to modulate processes involved in growth, the mechanistic basis of this regulation is not well understood.…”
Section: Ppm Family Estpsmentioning
confidence: 99%
“…Although there is no indication that the ribosome directly inserts a catalytic residue, there are also no convincing candidates in EFTu itself, as judged by crystal structures and mutational studies (168,169). It is also known that kirromycin and the closely related aurodox somewhat stimulate the GTPase activity of EF-Tu even in the absence of the ribosome (170). On this basis, the crystal structure of EF-Tu:GDP bound to aurodox suggests that a particular histidine residue (His84) might contribute to transition state stabilization during GTP hydrolysis (138).…”
Section: Interactions With Ef-tu and The 50s Subunitmentioning
confidence: 99%
“…Previous studies have shown that eEF1A is phosphorylated in response to different growth conditions (34,35). The negative impact on eEF1A function as a result of phosphorylation may be through defective aa-tRNA binding (36). Phosphoproteomic studies in S. cerevisiae have identified several conserved residues that are phosphorylated (37-39).…”
Section: Eef1a-ura3p F308l and S405p Strains Exhibit Increasedmentioning
confidence: 99%